PENGARUH SIGNAL DAN TRUST IN CAPABILITY OR COMPETENCE DIMENSION TERHADAP TRUST IN INTENTIONS AND VALUE DIMENSIONS PADA NOKIA SALES DAN CARE CENTER - VITA BRILIANA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2009)
The main purpose of the research is to examine the influence of signal, and trust in capability or competence dimension on trust in intentions and value dimensions. Data was collected using survey questionnaire distribution to 100 respondents. The respondent of the research is people who services their handphone. Data were analyzed using multiple regression analysis. The result showed that there is significant influence of signal, trust in capability or competence dimension on trust in intentions and value dimensions.